2021
DOI: 10.1371/journal.pone.0251214
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of potential COVID-19 recurrence in patients with late repeat positive SARS-CoV-2 testing

Abstract: Background SARS-CoV-2 reinfection and reactivation has mostly been described in case reports. We therefore investigated the epidemiology of recurrent COVID-19 SARS-CoV-2. Methods Among patients testing positive for SARS-CoV-2 between March 11 and July 31, 2020 within an integrated healthcare system, we identified patients with a recurrent positive SARS-CoV-2 reverse transcription polymerase chain reaction (RT-PCR) assay ≥60 days after an initial positive test. To assign an overall likelihood of COVID-19 recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 16 publications
1
21
0
1
Order By: Relevance
“…The most up-to-date research suggests that infection provides natural immunity for at least three months [ 13 ] and immunity remains stable up to 6–8 months after the initial infection [ 12 , 14 ]. Furthermore, the maximum duration of SARS-CoV-2 ribonucleic acid (RNA) shedding in the upper respiratory tract, indicating recurrence, has been reported to be between 83 and 104 days [ 15 18 ], meaning positive retesting after roughly 3 months of a prior positive PCR test, along with clinical criteria, favors confirmation of reinfection [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most up-to-date research suggests that infection provides natural immunity for at least three months [ 13 ] and immunity remains stable up to 6–8 months after the initial infection [ 12 , 14 ]. Furthermore, the maximum duration of SARS-CoV-2 ribonucleic acid (RNA) shedding in the upper respiratory tract, indicating recurrence, has been reported to be between 83 and 104 days [ 15 18 ], meaning positive retesting after roughly 3 months of a prior positive PCR test, along with clinical criteria, favors confirmation of reinfection [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…An even lower reinfection rate was reported by Utah investigators. In the relevant retrospective cohort, with a sample size of 23,176 COVID-19 patients, the rate of reinfection was as low as 0.04% [22]. In addition, an Iranian study reported a 0.33% re-infection/reactivation rate at one year post SARS-CoV-2 infection [23].…”
Section: Immunity After Sars-cov-2 Infection Versus Post Vaccinationmentioning
confidence: 98%
“…Recurrent infection with SARS-CoV-2 has been reported in a number of patients, although recurrent infection rates were relatively low (estimated to occur in 0.04% of all patients with COVID-19 in one US study [ 116 ]) prior to the emergence of the omicron variant. NAbs may play a role in treating patients with recurrent infections; however, treatment algorithms remain to be established.…”
Section: Expert Opinionmentioning
confidence: 99%